PRE herbicides influence critical time of weed removal in glyphosate-resistant corn. (17th April 2021) - Ulusoy, Ayse Nur; Osipitan, O. Adewale; Scott, Jon; Jhala, Amit J.; Lawrence, Nevin C.; Knezevic, Stevan Z.
Abstract: Residual herbicides applied PRE provide early season weed control, potentially avoid the need for multiple POST herbicides, and can provide additional control of herbicide-resistant weeds. Thus, field studies were conducted in 2017 and 2018 at Concord, NE, to evaluate the influence of PRE herbicides on critical time for postemergence weed removal (CTWR) in corn. The studies were arranged in a split-plot design that consisted of three herbicide regimes as main plot treatments and seven weed removal timings as subplot treatments in four replications. The herbicide regimes included no PRE herbicide, atrazine, and a premix of saflufenacil/dimethenamid-P mixed with pyroxasulfone. The weed removal timings were at V3, V6, V9, V12, and V15 corn growth stages and then plots were kept weed-free until harvest. A weed-free and nontreated control were included for comparison. The relationship between corn growth or yield, and weed removal timings in growing degree days (GDD) was described by a four-parameter log-logistic model. This model was used to estimate the critical time for weed removal based on 5% crop yield loss threshold. A delay in weed removal until the V2 to V3 corn growth stage (91 to 126 GDD) reduced corn biomass by 5% without PRE herbicide application. The CTWR started at V3 without PRE herbicide in both years. Atrazine delayed the CTWR up to V5 in both years, whereas saflufenacil/dimethenamid-P plus pyroxasulfone further delayed the CTWR up to the V10 and V8 corn growth stages in 2017 and 2018, respectively. Herbicide applied PRE particularly with multiple sites of action can delay the CTWR in corn up to a maximum growth stage of V10, and delay or reduce the need for POST weed management.